2021
DOI: 10.3390/met11050696
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Features and Surface Hardening of Ultrafine-Grained Ti-6Al-4V Alloy through Plasma Electrolytic Polishing and Nitrogen Ion Implantation

Abstract: This work studies a near-surface layer microstructure in Ti-6Al-4V alloy samples subjected to plasma electrolytic polishing (PEP) and subsequent high-energy ion implantation with nitrogen (II). Samples with a conventional coarse-grained (CG) structure with an average α-phase size of 8 μm and an ultrafine-grained (UFG) structure (α-phase size up to 0.35 μm) produced by equal channel angular pressing were used in the studies. Features of phase composition and substructure in the thin surface layers are shown aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Studies of the surface modification of titanium alloys also contributed a substantial part to the issue. Smyslova et al investigated near-surface layer microstructure of Ti-6Al-4V alloy samples subjected to plasma electrolytic polishing with subsequent high-energy nitrogen ion implantation [11]. It was found that the initial structural state of the Ti-6Al-4V alloy substrate had a significant effect on the transformation of the dislocation substructure during the treatment.…”
Section: Contributionsmentioning
confidence: 99%
“…Studies of the surface modification of titanium alloys also contributed a substantial part to the issue. Smyslova et al investigated near-surface layer microstructure of Ti-6Al-4V alloy samples subjected to plasma electrolytic polishing with subsequent high-energy nitrogen ion implantation [11]. It was found that the initial structural state of the Ti-6Al-4V alloy substrate had a significant effect on the transformation of the dislocation substructure during the treatment.…”
Section: Contributionsmentioning
confidence: 99%